Hubungan antara konsep kendiri dengan pencapaian akademik dalam kalangan pelajar tingkatan empat di daerah Lahad-Datu - Hamsiah, Yangkok (2010)
The aim of this study is to identify the level of student's self concept and academic achievement and its correlation. The correlation between six dimensions of self concepts and academic achievement is also examined. The level of self concept is measured as high or positive, average, and low or negative. The level of academic achievement is measured based on overall scores obtained during internal school examinations. The sample consists of 152 form four art stream secondary schools students who were chosen randomly from two schools in Lahad Datu, Sabah. This research identify dimensions of self concept that include physical, ethics and moral, personal, family, social and behavioral self concept. The instrument used was a questionnaire for self concept which was modified from Tennessee Self-concept Scale that was created by Fitts (1971) and comprises of 62 questions, which are scaled from 1 to 5 (Likert Scale) in order to measure the level of self-concept. The reliability value of Cronbach Alpha for the whole set of questionnaires used was α = 0.744. The results were analyzed by using the SPSS software version 12.0. Demography factors were analyzed using descriptive statistic analysis. Pearson's correlation test was used at the significant level of 0.05 to analyze the relationship between students' self concept and their academic achievement. The findings show that the student self-concept and their academic achievement is at the average level and there is a weak but significant relationship between their self-concept and academic achievement. The analysis also showed that the family self-concept and behavior self-concept dimensions indicated a significant and positive relationship with the students' academic achievement